In-hospital prognostic value of on admission creatinine clearance in patients with acute coronary syndrome - Saha, Madhurima; Khan, MM Zahurul Alam; Alam, Md Zahid; Faruq, Mohammad Omar; Ahsan, ASM Areef; Saha, Debasish Kumar (Bangladesh Critical Care Journal, 2015)
Objective: To find out association between creatinine clearance rate (CCR) and in-hospital outcome of acute coronary syndrome (ACS). Methodology: This prospective observational study was carried on 100 patients with acute coronary syndrome, in Coronary Care Unit (CCU) of BIRDEM General Hospital, Shahbag, Dhaka, over a period of six months from July 1, 2012 to December 31, 2012. Results: Subjects were divided into three groups (A:CCR>60,B :CCR-30-60and C:CCR<30) depending on their CCR (ml/min). Mean creatinine clearance rate was 56.15 (±29.57) ml/min and mean serum creatinine level was 3.68 (±2.59) mg/dl. Among 20 patients of Group A subjects 15(75%) were discharged in a stable condition. 2(10%) and 3(15%) patients developed isolated left ventricular failure (LVF) and isolated hypotension respectively. No patient died in this group and none of them developed any bleeding episode (epistaxis,melaena,haematemesis, haematochezia or per vaginal bleeding etc), sepsis or multi-organ dysfunction syndrome (MODS). Among 35 patients of Group B subjects 8(22.8%) were discharged in a stable condition. 9(25.7%) and 6(17.1%) patients developed isolated LVF and isolated hypotension respectively. 2(5.7%) patients died in this group and 7(20%), 2(5.7%),1(2.8%) patients developed bleeding episode, sepsis and MODS respectively. Among 45 patients of Group C subjects 3(6.6%) were discharged in a stable condition. 12(26.7%) and 8(17.7%) patients developed only LVF and only hypotension respectively . 4(8.8%) patients died in this group during their hospital stay and 11(24.4%), 3(6.6%) and 4(8.8%) patients developed bleeding episode, sepsis and MODS respectively. ANOVA test suggested that decreased creatinine clearance rate was significantly related to poor clinical outcome(P<0.05). Conclusion: This study showed that decreased creatinine clearance is directly related to poor outcome of acute coronary syndrome. So subjects with ACS should be closely monitored for decreased creatinine clearance rate to avoid life threatening complications. And subjects with renal impairment suffering from ACS should be closely observed as patients with decreased CCR has poor clinical outcome. Bangladesh Crit Care J March 2015; 3 (1): 3-6